PROSES KARBURASI PADA BAJA KARBON RENDAH DENGAN MENGGUNAKAN KARBON ARANG KAYU BELIAN DAN ARANG KAYU AKASIA - Muh Anhar (INOVTEK POLBENG, 2019)
Low carbon steel has extensive use in the construction field and is grouped into steel which can be processed with machinery (machinery steel). The prominent weakness of this material is the type of failure that often occurs in low carbon steel materials is wear, deformation, chopping, and breaking. The purpose of conducting this research is to find out the process of carburizing on (wood charcoal and acacia wood charcoal) on low carbon steel.This solid carburizing process uses a temperature of 900OC, with a hold time of 30 minutes. The material used is a mixture of wood charcoal with calcium carbonate and acacia wood charcoal with calcium carbonate. Tests carried out were rockwell hardness tests.The test results showed that the hardness of carbon steel which experienced carburizing treatment with acacia wood charcoal = 51.65 HRB. Hardness found in low carbon steel without treatment = 50.3 HRB. Hardness of wood charcoal = 50.6 HRB. Judging from the results above, the low carbon steel without treatment is smaller than carbon steel which is heat treated and carburized.